Outcomes after plating of olecranon fractures: A multicenter evaluation. Issue 7 (July 2016) - De Giacomo, Anthony F.; Tornetta, Paul; Sinicrope, Brent J.; Cronin, Patrick K.; Althausen, Peter L.; Bray, Timothy J.; Kain, Michael S.; Marcantonio, Andrew; Sagi, Claude; James, Chris R.
Abstract: Introduction: The aim of this study was to report the physical and functional outcomes after open reduction internal fixation of the olecranon in a large series of patients with region specific plating across multiple centres. Patients/methods: Between January 2007 and January 2014, 182 consecutive patients with a displaced olecranon fracture treated with open reduction internal fixation were included in this study. Retrospective review across four trauma centres collected elbow range of motion, DASH scores, hardware complications, and hardware removal. Postoperative visits in the outpatient clinic were at two, six, and twenty-four weeks. After 24 weeks, patients were eligible for hardware removal if symptomatic. All patients were contacted, at least 1 year following surgery, to determine if hardware was removed. Results: 182 patients (75 women, 105 men) average age 50 (16–89) with 162 closed and 19 open displaced olecranon fractures were treated with one region specific plate. Nineteen were lost to followup leaving 163 for analysis with all patients united. The most common deficiency was a lack of full extension with 39% lacking at least 10° of extension. Hardware was asymptomatic in 67%, painful upon leaning in 20%, and restricted activities in 11% resulting in a 15% rate of hardware removal. Hardware complaints were more common if a screw was placed in the corner of the plate ( P  = 0.004). When symptomatic, the area of the plate that was bothersome encompassed the whole plate in 39%, was at the edge of the plate in 33%, and was a screw head in 28%. The DASH scores, collected at final follow-up of 24 weeks, was 10.1 ± 16, indicating moderate disability was still present. Patients who lacked 10° of extension had a DASH of 12.3 as compared with 10.5 for those with near full extension, but this was not significant ( P  = 0.5). Conclusion: Plating of the olecranon leads to predictable union. The most common complication was lack of full extension with 39% lacking more than 10°, although this did not have any effect on DASH scores. Overall results indicate that disability still exists after 6 months with an average DASH score of 10. Level of evidence: Therapeutic level III.